2018
DOI: 10.1149/08614.0341ecst
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Neodymium Containing Chloride Melts with Oxygen Species

Abstract: Reaction of lithium oxide with neodymium chloride was studied in LiCl, LiCl–KCl and NaCl–KCl based melts at various O2– : Nd3+ mole ratios. The effect of the experimental conditions on the degree and rate of neodymium precipitation, phase composition of the solid reaction products was investigated. Size of the particles in the precipitates formed at various conditions was determined to assess the feasibility of subsequent separation of the solids from the technological melts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Rare earth fission products can be separated from the technological electrolytes by a number of means including precipitating them as sparingly soluble species. Alkali phosphates 6,7 or oxides 8,9 can be used as the precipitants. However, addition of a precipitating agent in a sufficient excess to enable complete precipitation of the rare earths inevitably results in altering the composition of the solvent melt that can hinder or complicate its subsequent reuse in the technological process.…”
mentioning
confidence: 99%
“…Rare earth fission products can be separated from the technological electrolytes by a number of means including precipitating them as sparingly soluble species. Alkali phosphates 6,7 or oxides 8,9 can be used as the precipitants. However, addition of a precipitating agent in a sufficient excess to enable complete precipitation of the rare earths inevitably results in altering the composition of the solvent melt that can hinder or complicate its subsequent reuse in the technological process.…”
mentioning
confidence: 99%
“…16−18 According to several studies, rare earth elements can be precipitated from various molten salts using different precipitants such as alkali phosphates 19,20 and oxides. 21,22 One advantage of gaseous oxygen or oxygen compounds is that they do not introduce any additional metallic cations into the melt. Several studies have been published recently concerning the reaction of oxygen within the 3LiCl−2KCl eutectic melt containing rare earth chlorides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While several reports have been published demonstrating the recovery of rare earth metals from end-of-life products, as well as samarium and cobalt from Sm–Co magnets, all the reported studies are based on aqueous or non-aqueous solvent extraction processes that use water or organic solvents. Recently, ionic melts of molten chlorides have become an attractive reaction medium in many fields including nuclear energy, metallurgy, clean synthesis, catalytic processes, and thermal energy storage. According to several studies, rare earth elements can be precipitated from various molten salts using different precipitants such as alkali phosphates , and oxides. , One advantage of gaseous oxygen or oxygen compounds is that they do not introduce any additional metallic cations into the melt. Several studies have been published recently concerning the reaction of oxygen within the 3LiCl–2KCl eutectic melt containing rare earth chlorides. It has been shown that bubbling oxygen through solutions of LnCl 3 in the chloride melt at 450–750 °C resulted in the formation of LnOCl (Ln = La, Pr, Nd, Eu, and Gd), CeO 2 , and PrO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of oxygen (as O 2 or oxide-ions) with solutions of rare earth chlorides in chloride melts was fairly well investigated. [1][2][3][4] Depending on the experimental conditions the reaction led to precipitation of rare earths as oxychlorides or oxides, with higher temperatures favoring the oxide formation. 2,4 Low solubility of rare earth oxides in halide melts 5,6 allows proposing this method, for example, for removing rare earth fission products from chloride electrolytes.…”
mentioning
confidence: 99%